(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Relative abundance and diversity of insects were studied in the four spots of Chittagong University Campus, from October 2015 to September 2016. The studied insect orders were- Odonata, Orthoptera, Coleoptera, Hymenoptera and Lepidoptera. Two families under Odonata, four under Orthoptera, five under Coleoptera, three families under Hymenoptera and eight under Lepidoptera were examined from the four study spots. Among these, sixteen species of Odonata, eight species of Orthoptera, Coleoptera and Hymenoptera in each and 32 Lepidoptera species were identified. Highest numbers of insects (276) was collected in April’16 and December’15 whereas lowest numbers of insects (201) were collected in October’15. The highest abundance (906) of insects was found in Spot 3 (Hilly area), medium (785) in Spot 1 (Pond area) and lowest (642) and (648) in Spot 2 (Garden area) and Spot 4 (Artificial forest area), respectively. Lepidoptera (1217) was the most dominant order in the four studied spots followed by Odonata (636), Coleoptera (395), Hymenoptera (381) and Orthoptera (352). The average highest species richness, species diversity and species evenness were observed in October’15 (2.40 ± 0.11), August’16 (2.22 ± 0.03) and August’16 (0.96 ± 0.01), respectively and lowest in April’16 (2.18 ± 0.04), April’16 (1.98 ± 0.07) and April’16 (0.85 ± 0.03), respectively. During the study period, the highest species richness was observed in Spot 2 and Spot 4 (2.32 ± 0.03) and lowest in Spot 3 (2.13 ± 0.02); the highest species diversity was observed in Spot 3 (2.16 ± 0.02) and lowest in Spot 1 and Spot 2 (2.04 ± 0.03); and the highest species evenness was observed in Spot 3 (0.93 ± 0.01) and lowest in Spot 1 and Spot 2 (0.88 ± 0.01). Abundance and diversity of insects were dependent on seasonal fluctuation, and also on ecological and environmental conditions. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 55-64